Microvascular changes at different stages of chronic kidney disease - Kannenkeril, Dennis; Frost, Shaun; Nolde, Janis M.; Kiuchi, Márcio Galindo; Carnagarin, Revathy; Lugo-Gavidia, Leslie Marisol; Chan, Justine; Joyson, Anu; Matthews, Vance B.; Herat, Lakshini Y.; Azzam, Omar; Mehdizadeh, Maryam; et al. (Journal of Clinical Hypertension, 2020)
Patients with progressing chronic kidney disease (CKD) are more likely to experience cardio- and cerebrovascular events than progressing to end-stage renal disease. The authors explored whether retinal microvascular calibers differed with the degree of renal impairment and between the standard and extended optic disk and may serve as a simple additional tool for risk stratification in this highly vulnerable patient cohort. The authors analyzed central retinal arteriolar and venular equivalent calibers (CRAE, CRVE) at different retinal zones (zone B&C) using digital retinal imaging in hypertensive patients with stage 2 (n = 66) or stage 3 CKD (n = 30). Results were adjusted for age, sex, HbA1c, and 24-hour diastolic blood pressure. Mean eGFR was 77.7 ± 8.9 and 48.8 ± 7.9 ml/min/1.73 m2 for stage 2 and 3 CKD, respectively. CRAE and CRVE in zones B and C were significantly lower in patients with stage 3 CKD compared to patients with stage 2 CKD (CRAE-B:141.1 ± 21.4 vs. 130.5 ± 18.9 µm, p =.030; CRAE-C:137.4 ± 19.4 vs 129.2 ± 18.2 µm, p =.049; CRVE-B:220.8 ± 33.0 vs. 206.0 ± 28.4 µm, p =.004; and CRVE-C:215.9 ± 33.0 vs. 201.2 ± 25.1µm, p =.003). In patients with stage 2 CKD, CRAE-B was higher than CRAE-C (141.1 ± 21.4 vs. 137.4 ± 19.4µm, p <.001). In contrast, such a difference was not found in patients with stage 3 CKD. CRAE of both retinal zones correlated with eGFR for the entire cohort. In patients with stage 3 CKD, retinal narrowing is more pronounced compared to patients with stage 2 CKD. Whether the novel observation of difference in arteriolar caliber between zones B and C in stage 2 CKD could serve as an early marker of CKD progression warrants further investigation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: chronic kidney disease; glomerular filtration rate; microvascular change; retinal vessel caliber hypertension sympathetic nervous system